Influence of workload and weather conditions on rolling behaviour of horses and mules - Luz, Marina P.F. [UNESP]; Maia, Caroline M.; Gonçalvez, Heraldo César [UNESP]; Puoli Filho, José Nicolau P. [UNESP] (Elsevier, 2021)
We evaluated the influences of workload intensity, bath handling and environmental conditions in the rolling behaviour of horses and mules. For this purpose, animals were observed after being exposed to different levels of workload and the rolling behaviour was recorded and described. During all testing procedures, the weather condition (temperature and humidity) was registered by a Black globe and Wet Bulb apparatus. Horses frequently rolled after intense exercise and after bath handling, independently of the weather condition. Mules frequently rolled after control (no exercise) and intense exercise in warmer and wetter days and after bath handlings in colder and drier days. Rolling behaviour characteristics were slightly different between species. While mules exhibited more frequently the behaviours of rest, self-care, yawn, tail swishing, complete spins, snort vocalization and use of the same spot to roll, horses exhibited more frequently the behaviours of paw, sniff, head and neck rubbing movements and incomplete spins to the right and left. This findings evidence that rolling is an important and frequently exhibited behaviour by domestic horses and mules, but animals may express it differently and may have their own motivations. In this sense, we believe that domestic equines, mainly those raised in more intensive livestock, should have the opportunities to freely express the rolling, as a way to improve their welfare conditions and with agreement with a more rational handling practice.
Keywords: Horses; Mules; Rolling; Temperature; Workload